Service Learning in Higher Education: Impact Evaluation and Best Practices - Putra, Feby Arma; Annas, Nafiz; Reni, Reni (Journal Ligundi of Community Service, 2024)
Background: Service learning in higher education integrates community service with academic instruction, fostering a sense of civic responsibility while enhancing students' learning experiences. Despite its growing popularity, the impact and best practices of service learning programs are not uniformly understood. Evaluating these programs' effectiveness is essential to maximize their benefits for students, institutions, and communities. Objective: This study aims to evaluate the impact of service learning on student outcomes and identify best practices for implementing these programs in higher education. The research focuses on understanding how service learning influences students' academic performance, personal development, and civic engagement. Methods: A mixed-methods approach was used, combining quantitative surveys and qualitative interviews. Quantitative data were collected from 500 students across various universities who participated in service learning programs, measuring their academic performance, personal growth, and civic engagement. Qualitative interviews with 30 program coordinators provided insights into the best practices and challenges of implementing these programs. Data were analyzed using statistical methods for the surveys and thematic analysis for the interviews. Results: Findings indicate that students who participated in service learning programs showed significant improvements in academic performance, personal development, and civic engagement compared to those who did not participate. Best practices identified include structured reflection activities, strong community partnerships, and integration of service experiences with academic content. Challenges such as resource constraints and varying levels of student engagement were also highlighted. Conclusion: Service learning in higher education has a positive impact on students, enhancing their academic, personal, and civic development. Implementing best practices can further optimize these benefits, though challenges remain. Future research should explore long-term impacts and strategies to overcome implementation barriers.